The "real value" of field trips in the early weeks of higher education: the student perspective. Issue 1 (1st January 2017) - Larsen, C.; Walsh, C.; Almond, N.; Myers, C.
Abstract: The benefits attributed to field trips by science educators are: social development; observation and perception skills; giving meaning to learning; providing first-hand experience and stimulating interest and motivation. Arguably, the "real value" of field work is attributed by students. In this study, 100 first-year students took part in an analysis of the value of a residential field trip. The field trip was a purposeful combination of personal development and academic activities. Pairwise comparison showed that the attributed value score for "Personal and Social Development" was significantly higher than scores for "Provide First-hand Experience" and "Observation and Perception Skills". The attributed value for "Stimulate Interest and Motivation in the Subject" also scored more highly than "Provide First-hand Experience", and "Observation and Perception Skills"; "Give meaning to Learning" was significantly higher than that for "Observation and Perception Skills". In addition, the "educator" was also able to significantly improve students' scores for "Stimulate Interest and Motivation". This insight into students' perceptions of field work recasts our thinking as educators; social capital is a key factor in student persistence and subsequence academic success. Field trips should be considered a valuable addition to retention strategies in a way that is tangible for students themselves.